Political Perspectives on the Quality of Healthcare Services: A Literature Review - Muhammad Alwy Arifin; Ryryn Suryaman Prana Putra (Journal of Health Literacy and Qualitative Research, 2024)
The quality of healthcare services is a critical determinant of health outcomes and public satisfaction. Political perspectives significantly influence the quality of healthcare through policy-making, funding, and regulation. This literature review examines the interplay between political ideologies, policy decisions, and healthcare quality. It explores how different political systems and party ideologies affect healthcare quality, the role of political will and governance in shaping healthcare policies, and the impact of political instability on health systems. The review also discusses how political agendas, lobbying, and public health advocacy shape healthcare quality. The findings underscore the need for a nuanced understanding of political factors in improving healthcare services and achieving equitable health outcomes.